2020
DOI: 10.18632/aging.103364
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a novel risk score model by comprehensively analyzing the immunogen database of bladder cancer to indicate clinical significance and predict prognosis

Abstract: Background: Bladder cancer (BCa) has the highest incidence of aggressive malignant tumors in the urogenital system and is the ninth most common cancer worldwide. Immune function-related genes (IFRGs), which are plentiful in immune cells and the immune microenvironment (IME), have the potential to assess prognosis and predict the efficacy of immunotherapy. A complete and significant immunogenomic analysis based on abundant BCa genetic samples from The Cancer Genome Atlas (TCGA) will provide insight into the fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 41 publications
1
13
0
Order By: Relevance
“…but its expression and function in BC are still unclear. Recently, some studies have used databases to analyze the prognostic relevance of Rac3 in BC [23][24][25][26][27], but strict inclusion criteria were in place for the patients with BC in this study, and the number of patients we analyzed was different. We first performed Kaplan-Meier survival analysis, followed by univariate and multivariate Cox analysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…but its expression and function in BC are still unclear. Recently, some studies have used databases to analyze the prognostic relevance of Rac3 in BC [23][24][25][26][27], but strict inclusion criteria were in place for the patients with BC in this study, and the number of patients we analyzed was different. We first performed Kaplan-Meier survival analysis, followed by univariate and multivariate Cox analysis.…”
Section: Discussionmentioning
confidence: 99%
“…We first performed Kaplan-Meier survival analysis, followed by univariate and multivariate Cox analysis. Qiu et al [23] and Liu et al [24] screened only prognostic immune-related genes with univariate Cox analysis, while Na et al [25] and Tang et al…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We used the remaining 3 mRNAs (ME1, MED10, and MED22) to construct a prognostic model. The use of risk scores can facilitate a more accurate prediction of patient prognosis and guide clinical decision making [27]. An overwhelming number of genes have been identified as potential prognostic biomarkers for cancer [28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“… 14 The existing body of research on bladder cancer suggests EDNRA is one of immune function-related genes, and has the potential to assess prognosis and predict the efficacy of immunotherapy. 15 Wei et al observed that EDNRA expression can be downregulated by miR-200c in regulation of gastric carcinoma cells proliferation, apoptosis and invasiveness. 16 However, the prognosis value of EDNRA expression and its correlation with TME in patients with STAD remains unclear.…”
Section: Introductionmentioning
confidence: 99%